The Gospel according to Luke - Patella, Michael, 1954- (Collegeville, Minn. : Liturgical Press, 2005)
"Complete biblical texts with sound, scholarly based commentary that is written at a pastoral level; the Scripture translation is that of the New American Bible with Revised New Testament and Revised Psalms (1991)"--Provided by publisher.
Keywords: Bible. -- Commentaries